The type VI secretion system sheath assembles at the end distal from the membrane anchor - Vettiger, Andrea (Nat Commun, 2017)
The bacterial Type VI secretion system (T6SS) delivers proteins into target cells using fast contraction of a long sheath anchored to the cell envelope and wrapped around an inner Hcp tube associated with the secreted proteins. Mechanisms of sheath assembly and length regulation are unclear. Here we study these processes using spheroplasts formed from ampicillin-treated Vibrio cholerae. We show that spheroplasts secrete Hcp and deliver T6SS substrates into neighbouring cells. Imaging of sheath dynamics shows that the sheath length correlates with the diameter of spheroplasts and may reach up to several micrometres. Analysis of sheath assembly after partial photobleaching shows that subunits are exclusively added to the sheath at the end that is distal from the baseplate and cell envelope attachment. We suggest that this mode of assembly is likely common for all phage-like contractile nanomachines, because of the conservation of the structures and connectivity of sheath subunits.